Geomorphology and Paleoseismology of the Weinan Fault, Shaanxi, Central China, and the Source of the 1556 Huaxian Earthquake. Issue 12 (8th December 2020) - Feng, X.; Ma, J.; Zhou, Y.; England, P.; Parsons, B.; Rizza, M. A.; Walker, R. T.
Abstract : The 1556 CE Huaxian earthquake resulted in an estimated 830, 000 deaths and caused widespread devastation in the Weihe Basin, China. Seismic intensities from historical accounts yield, via magnitude‐intensity relations, a commonly quoted magnitude of 8¼ to 8½. The maximum recorded shaking was confined to a zone close to the Huashan and Weinan faults, which exhibit fresh scarps up to 7–8 m high. Recent palaeoseismic studies have suggested, however, that the Weinan fault has not ruptured at the surface for several thousand years. Furthermore, the 90‐km combined length of the Huashan and Weinan faults is short for an earthquake of magnitude 8¼ to 8½. We present a detailed analysis of the Weinan fault at one well‐preserved site, combining field observations and age constraints from fluvial terraces displaced by faulting, analysis of a high‐resolution digital elevation model (DEM), interpretation of the walls of a quarry that cuts through the fault zone, and from a profile of borehole cores across the fault. We find that the fault ruptured within the last 900 years and is likely, along with the Huashan segment, to be the causative fault for the 1556 earthquake. The magnitude remains uncertain, with M w 7.5 being a plausible estimate given the fault length, and no more than M w 8.0 if we use the maximum estimates of slip. These estimates are considerably smaller than magnitudes estimated from intensities, with importance in estimating the recurrence intervals between destructive earthquakes and hazard across central China. Key Points: The 1556 CE Huaxian earthquake of central China likely occurred on the Weinan‐Huaxian faults It potentially involved slip of up to 10 m over a length of 90 km; its magnitude ( M w ) was likely 7.5 to a maximum of 8.0 We suggest that historical magnitude from intensities overestimates the size, with implications for seismic hazard estimates in China